2017
DOI: 10.1051/bioconf/20170901017
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of Anthracnose in resistant varieties (PIWI) in the high altitude regions of southern Brazil

Abstract: The objective of this study was to evaluate the different degrees of tolerance to Anthracnose infection in three PIWI varieties (Cabernet Cortis, Regent and Bronner) compared to the Cabenert Sauvignon variety. The experiment was conducted at EPAGRI Experimental Station, located in the city of São Joaquim, Santa Catarina State (28 • 17 39 S; 49 • 55 56 W, altitude 1,415 m a.s.l.), during 2016/2017 growing season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Field studies on the performance of fungus resistant varieties are scarce in the literature [46][47][48][49][50] and, as noted above, the resistance of PIWI cultivars varies not only with genetics but also with location [10], so comparisons should be taken with caution. For instance, one of the most comprehensive studies was the one by Zamboni et al [51], who evaluated the adaptability of 26 resistant varieties in terms of yield, quality and resistance against fungal diseases to Emilia-Romagna hills (Ravenna, Italy) over a 5-year period (1994-1998).…”
Section: Discussionmentioning
confidence: 99%
“…Field studies on the performance of fungus resistant varieties are scarce in the literature [46][47][48][49][50] and, as noted above, the resistance of PIWI cultivars varies not only with genetics but also with location [10], so comparisons should be taken with caution. For instance, one of the most comprehensive studies was the one by Zamboni et al [51], who evaluated the adaptability of 26 resistant varieties in terms of yield, quality and resistance against fungal diseases to Emilia-Romagna hills (Ravenna, Italy) over a 5-year period (1994-1998).…”
Section: Discussionmentioning
confidence: 99%
“…planta -1 ), medidas preventivas de controle devem ser adotadas para controlar a alta intensidade de antracnose (WURZ et al 2017). Bonin et al (2017) verificaram que cultivares PIWI como Cabernet Cortis, Regent e Bronner, que apresentam resistência genética ao míldio, não apresentam resistência à antracnose. Neste caso, o míldio tende a ocupar o lugar de uma doença de importância secundária e, portanto, a antracnose poderá tornar-se uma doença de importância primária.…”
Section: Agente Causal Sintomatologia E Epidemiologiaunclassified
“…Regarding to downy mildew resistance, Zanghelini et al (2018) indicated that cultivars 'Calardis Blanc', 'Felicia' e 'Helios', had a partial resistance to downy mildew in the climatic conditions of Santa Catarina State. Bonin et al (2017) observed that PIWI cultivars 'Bronner', 'Cabernet Cortis' and 'Regent' showed little resistance to Anthracnose. And finally, De Bem et al ( 2020) in a study carried out in the region of Trento, in northern Italy, found that the white PIWI varieties Muscaris and Jasmine showed a high degree of resistance to downy mildew, while Bronner, Pӧlӧskei Muscotály and Solaris showed intermediate resistance and Bianca presented the highest susceptibility to downy mildew.…”
Section: Introductionmentioning
confidence: 98%
“…One of the advantages of these varieties is the reduction of the number of pesticide applications (FULLER et al 2014), especially in warm humid areas such as southern Brazil. The use of PIWI cultivars can be considered an option for Brazilian growers, as a way to reduce the use of pesticides, consequently reducing costs and improving grape quality (DE BEM et al, 2016;BONIN et al, 2017). Also, more recent wine tastings have shown that it is possible to make wine from these varieties with a quality similar to that of traditional varieties (BASLER;PFENNINGER, 2003).…”
Section: Introductionmentioning
confidence: 99%